Electrocardiogram in corrected transposition of the great vessels of the bulbo-ventricular inversion type - Fernández, F. (1970)
Twenty cases of corrected transposition of the great vessels of the bulbo-ventricular inversion type, either lone or combined with other intracardiac anomalies, were analysed. Rhythm and/or atrio-ventricular conduction disturbances were common to all groups of cases. QRS pattern changes were found to be related both to ventricular inversion and to ventricular hypertrophy. Isolated corrected transposition and corrected transposition with systemic ventriculo-atrial regurgitation give rise to tracings suggestive of systemic ventricular hypertrophy. Corrected transposition of the great vessels with pulmonary stenosis or pulmonary artery hypertension is usually accompanied by the electrocardiographic signs of a venous-ventricular hypertrophy, with a characteristic inversion of the normal praecordial pattern. The conventional criteria of ventricular hypertrophy may be applied in corrected transposition of the great vessels but are less reliable than in cases without ventricular inversion. The so-called electrocardiographic pattern of `ventricular inversion' in this anomaly is related not only to the inverted position of the ventricles but to a greater extent to the predominant, anatomically left, venous-ventricular hypertrophy which re-establishes the normal weight ratio between the anatomically right and anatomically left ventricles.